Mathematics Learners’ Performance and Academic Achievement at a Public High School Institution in Leyte, Philippines - Jomar Cobacha Cabuquin; Ferdinand Tesado Abocejo (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2023)
This study examined the correlation between mathematics performance and academic achievement of junior high school learners in a government-run laboratory high school institution and compared the mathematics performance and academic achievement of male and female learners. Correlational and comparative research designs were employed to analyze the gathered secondary data. Findings revealed a positive and highly significant correlation between the learners' mathematics performance and academic achievement, indicating that high school learners who are adept in mathematics tend to succeed and perform better in their academic courses. Whereas low performance in mathematics correspondingly connotes low achievement in overall academic abilities. No significant difference was found between male and female learners, suggesting that both genders of learners can succeed academically. The study concludes that mathematics performance and academic achievement go hand in hand, while gender does not affect the learners' ability to excel in mathematics. Effectively, secondary learning institutions must provide mathematics learners with learning opportunities during Mathematics classes and classroom activities regardless of gender. Teachers must help learners understand how to solve problems and think critically, expose them to real-world applications, and build their confidence and motivation to excel academically.Â